Learning and Transforming with Planetary Futures - Balcom Raleigh, Nicolas (Birkhäuser Verlag, 2025)
The data is clear: Global warming is happening. Yet, there is a large gap between how soon we need to end and reverse greenhouse gas emissions and the implementation of transformative innovations at sufficient scale to do so. This chapter proposes we can learn how to increase collective climate action by integrating Planetary Futures produced via data and computation with mind-driven acts of imagination, reflection upon our relationships with others, and attention to meaning-making. It tours some of the recent developments in data availability and advanced computing and presents a selection of already existing data-driven projects which can produce models of Planetary Futures. To encourage learning from these resources, an argument is made for developing the capability called Futures Literacy (cf. Riel Miller) which pertains to the production and use of such models and conceptualizes them as one form, out of many, of a socio-biological phenomena called Anticipation (cf. Robert Rosen). While growing Futures Literacy takes time and patience, a small practical exercise is offered for practicing imagining specific and situated Planetary Futures to reach outcomes such as reflecting upon how people can appreciate novelty. It concludes with reflections upon how utilizing both computationally and non-computationally derived Planetary Futures, we can know more about our current circumstances, our relationships to others, and our sense of why addressing the climate emergency matters.
Practices of Futurecasting : Ways of sharing imagined tomorrows